ANALYSIS OF FACTORS AFFECTING THE SATISFACTION OF SELECTION OF ACCOUNTING STUDY PROGRAMS BY ACCOUNTING STUDENTS IN SURABAYA - Maria, Margareth Lily; Magdalena, Angeleen (Jurnal Pijar, 2025)
The purpose of this study is to analyze the factors that influence students majoring in Accounting in Surabaya in choosing an Accounting study program. The research method used is a survey with a quantitative approach, where data is collected through questionnaires given to students at several universities in Surabaya. The factors studied include personal motivation, career prospects, the impact of the social environment, and the quality of education. The findings of the analysis show that personal motivation and career prospects are important factors that influence students' decision to enroll in an accounting study program. This research offers valuable insights for educational institutions to better understand